2022
DOI: 10.3390/biology11050714
|View full text |Cite
|
Sign up to set email alerts
|

Hotspot siRNA Confers Plant Resistance against Viral Infection

Abstract: A hallmark of antiviral RNA interference (RNAi) is the production of viral small interfering RNA (vsiRNA). Profiling of vsiRNAs indicates that certain regions of viral RNA genome or transcribed viral RNA, dubbed vsiRNA hotspots, are more prone to RNAi-mediated cleavage for vsiRNA biogenesis. However, the biological relevance of hotspot vsiRNAs to the host innate defence against pathogens remains to be elucidated. Here, we show that direct targeting a hotspot by a synthetic vsiRNA confers host resistance to vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A certain level of protection against geminiviruses was obtained until now with dsRNAs, mainly when they were applied together with the viral inoculum (this study; [ 20 , 39 , 41 ]); no protection was observed when the virus is delivered through viruliferous whiteflies on plants treated with dsRNAs 24 h before [ 24 ]. The contrasting results could be partially related to the poor systemic translocation and movement of the naked dsRNAs in plants.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A certain level of protection against geminiviruses was obtained until now with dsRNAs, mainly when they were applied together with the viral inoculum (this study; [ 20 , 39 , 41 ]); no protection was observed when the virus is delivered through viruliferous whiteflies on plants treated with dsRNAs 24 h before [ 24 ]. The contrasting results could be partially related to the poor systemic translocation and movement of the naked dsRNAs in plants.…”
Section: Discussionmentioning
confidence: 94%
“…In this case, only a limited protection against viral infection would be guaranteed. The use of selected exogenous ds-sRNAs targeting the viral sRNAs hot spots could be evaluated as a possible more efficient alternative, as highlighted in the pathosystem N. benthamiana /African cassava mosaic virus [ 39 ]. Indeed, it seems that the vast majority of sRNAs generated by external dsRNAs have non-canonical AGO-incompatible sizes and that only a small fraction of external dsRNAs is processed by DCL2 and DCL4 into AGO2 and AGO1-compatible siRNA duplexes [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the vsiRNA pattern of virus-infected plants has shown that specific genomic regions give rise to greater numbers of vsiRNAs, termed RNA silencing 'hotspots' [7]. In practice, the characteristics of virus-specific siRNAs can be used for developing induced virus resistance [7][8][9], with hotspot regions being first choice of template for the artificial production of vsiRNAs against selected pathogens [10].…”
Section: Introductionmentioning
confidence: 99%